BIOTURBATOR SEBAGAI PEREKAYASA EKOSISTEM DI PESISIR DAN LAUTAN - Allsay Kitsash Addifisyukha Cintra (Pusat Penelitian Oseanografi LIPI, 2021)
A bioturbator is a biota that can change sediment either directly or indirectly through stirring particles and/or moving water. Changes in the sediment affect the resources that will affect the existence of other organisms. This paper aims to explain bioturbators and their roles as ecosystem engineers in coastal and marine environments. Bioturbators are classified into two main groups, namely reworking organisms and burrow ventilation organisms. Bioturbator affects the biogeochemistry of sediment and the sediment physical structure, both of which cause the formation of new habitats that can be used by other organisms. This, in turn, will affect the structure of the benthic community. It is necessary to understand how bioturbators work and how big their effect is so that they can be used for habitat conservation and restoration in the future.